Aldimines and ketimines as initiators in hardener systems and corresponding resin compositions for uses including fixing technology - WEINELT CHRISTIAN; SCHLENK CHRISTIAN; VOGEL MARTIN; STEURER PAUL; GRUN JURGEN (2018)
Hardener system for a synthetic resin composition comprising free-radically polymerizable compounds, including the following constituents: a) at least one activator in the form of a metal salt and, asfree-radical initiator b1) (i) at least one aldehyde and/or ketone and at least one primary amine, and/or b2) (ii) at least one aldimine or (iii) at least one ketimine, or a mixture of two or more ofconstituents (i) to (iii), and also synthetic resin compositions comprising such a hardener system for uses principally in fixing technology, and subjects of the invention associated therewith. 用于包含可自由基聚合的化合物的人造树脂组合物的固化剂体系，其包含下列成分：a)至少种以金属盐形式的活化剂；和作为自由基起始剂的b1)(i)至少种醛和/或酮和至少种伯胺，和/或b2)(ii)至少种醛亚胺或(iii)至少种酮亚胺，或成分(i)至(iii)中两种或更多种的混合物；以及尤其用于固定技术中的包含此类固化剂体系的人造树脂组合物；以及与此相关的发明主题。